Assessment of Annual Effective dose and radiological hazards associated with radioactivity on workers in Physics Laboratory - Rozhan Dilshad Haider; Dilshad Salih Ismael (Zanco Journal of Pure and Applied Sciences, 2023)
Determining the Excess Lifetime Cancer Risk (ELCR) and Annual Effective Dose Equivalent (AEDE) due to ionizing radiation that affects the faculty and students working in the Nuclear and solid-state Undergraduate Laboratories, College of Science, Salahaddin University -Erbil was the objective of this study. In this study, it was used two separate portable nuclear radiation detectors; the (INSPECTXUSB) and (DKG-21) Geiger counter nuclear radiation detectors. Equivalent Dose Rate (DER) and Absorbed Dose Rate (ADR) values were measured in (μSv/h) for radioactive sources (Am241, Cs137, Co60, Na22 and Sr90) and X-rays were radiated in three different devices. The results of (ELCR) were compared with the values listed in the UNSCEAR 2008 and ICRP world safety recommendations. The results indicated that the students experienced no substantial health risks, and the exposure doses are within the permissible limit except Sr90 (2.665±0.044) and the X-ray emitted from Phywe Systeme (4.758±0.014). Moreover, the hot spots of Cs137, Sr90 and X-ray and should be closely monitored. Since the staff personnel spend more time in the lab than students, they are more likely to be exposed to radiation and contamination Cs137 (3.297±0.030), Sr90 (15.988±0.261) and X-ray (28.551±0.045).